Have we got the optimal treatment for refractory Kawasaki disease in very young infants? A case report and literature review - Robert Lersch; Guido Mandilaras; Meike Schrader; Felicitas Anselmino; Nikolaus A. Haas; André Jakob (Frontiers Media S.A., 2023)
A small group of patients with Kawasaki disease (KD) demonstrates resistance to standard therapy, putting them at high risk for an unfavorable prognosis, especially regarding coronary artery aneurysms. Although adding corticosteroids to first-line i.v. immunoglobulins (IVIGs) is considered beneficial, and despite timely treatment initiation, very young infants, in particular, can present an unfavorable clinical course. We report on a 3-month-old boy with a clinically severe KD phenotype involving the early development of giant coronary artery aneurysms. Because of his poor response to the first course of IVIG and prednisolone, we administered infliximab. His clinical condition improved after that, and his temperature dropped. Inflammatory markers however did not recover completely, and he remained subfebrile. In addition, as the coronary artery dimensions deteriorated, a second IVIG course was administered and prednisolone continued at the initial dosage. Although fever and routine inflammatory parameters normalized, close follow-up investigations revealed both still increasing coronary artery dimensions and renewed rise in inflammatory parameters, necessitating two more infliximab administrations in addition to continuous prednisolone. Because of the coronary artery dimensions (left anterior descending artery, 4.9 mm, Z-score 11.1; right coronary artery 5.8 mm, Z-score 15.5), dual platelet inhibitory therapy with ASA and later clopidogrel combined with low-molecular heparin was indicated. Four weeks after his initial KD diagnosis, we detected no renewed increase in inflammatory markers; at that time, we observed a slight reduction in coronary dimensions. In summary, despite timely guideline-fulfilling therapy, the prolonged clinical course of this very young infant with KD entailing the development of giant coronary artery aneurysms makes us question whether this age group may benefit from early, even more intense therapy.